Stolen nights with the king - Kendrick, Sharon (Harlequin presents, 2022)
"As a child, servant's daughter Rosie Forrester adored her friend Prince Corso. Now he's a high-and-mighty king? Not so much! Yet his demand that she attend an international royal tour with him can't be denied--and neither can their chemistry! Their passionate tryst can only ever be temporary--Corso has to marry a woman of noble blood. It's a good thing virgin Rosie has vowed never to believe in the illusion of love. But as their time runs out, will their stolen nights together be enough?" -- Page [4] cover.